KONEKTIVITAS PENGEMBANGAN PARIWISATA MELALUI KONSEP RUTE WISATA DI CIAYUMAJAKUNING (Cirebon, Indramayu, Majalengka, dan Kuningan) - Mira Maharani (UHN IGB Sugriwa Denpasar, 2021)
At present, the existence of a highway that connects Cikopo-Palimanan-Kanci-Pejagan has become one of the factors that have a big influence on tourism in CIAYUMAJAKUNING, this is growing rapidly because now the CIAYUMAJAKUNING area is one of the preferred tourist destinations for tourists from Jakarta every weekend. apart from Bandung. It is hoped that tourism development in CIAYUMAJAKUNING will be able to contribute to the increase in the number of tourist visits and the spread of tourists that are not only focused on the city of Cirebon. The purpose of this research is to develop tourism through the tourist route of the Ciayumajakuning area. The approach used in this study is a qualitative and quantitative approach which are both carried out for the availability of data and different conditions according to the needs of the analysis. There are approximately 22 tourist attractions in Ciayumajakuning, but only 13 tourist attractions have been selected as priority tourist attractions that are included in the Ciayumajakuning tourist route. In selecting this strategic tourist attraction using the 5A concept. After selecting a strategic tourist attraction, a new tourist route will be arranged. The tourist route in Ciayumajakuning is divided into 3, namely the City Tour Route; Western Tourist Routes; and East Tourism Route, after the formulation of the tourist route, it is also necessary to analyze the supporting infrastructure needed for the tourist attractions included in the tourist route so that the tourist attraction will develop better and be more ready to receive tourists coming.